Comparison of APGAR Score of Newborns with Mode of Delivery and Its Associated Factors - Paudyal, Laxmi (International Journal of Social Sciences and Management, 2020)
Newborn baby should be assessed immediately soon after the birth and the APGAR (Appearance, Pulse, Grimace, Activity, Respiration) score is the most commonly used, simple and most effective method of immediate newborn assessment. The aim of the study was to compare the newborn APGAR score on first and fifth minute in two different mode of delivery; Normal Vaginal delivery (NVD) and Cesarean Delivery (CD) and its contributing factors. A cross-sectional study design with comparative research approach was adopted to conduct the research. Total 200 singleton babies (100 NVD and 100 CD) were selected and APGAR score was checked in the first and fifth minutes from baby’s birth record. Data were analyzed using descriptive and inferential statistics. Results showed that 88 and 95 percentage of neonatal APGAR scores in 1st and 5th minutes were more than seven, respectively. There were no significant statistical differences between APGAR score of 1st and 5th minutes in two methods of delivery (t=0.067 and 0.066 on 1st minute and 5th minute respectively, p>0.05). However, premature newborns, low birth weight, mother’s age and weight of mother, no of parity has effect on APGAR score. The study findings concluded that not the method of delivery has any effect on the low Apgar score of babies on birth but the factors such as prematurity, maternal age, mother’s weight, no of parity, low birth weight has significant association on low APGAR score of babies. Int. J. Soc. Sc. Manage. Vol. 7, Issue-3: 176-182